1978
DOI: 10.1007/bf01320072
|View full text |Cite
|
Sign up to set email alerts
|

Structural elements in adenovirus cores. Studies by means of freeze-fracturing and ultrathin sectioning

Abstract: Rod-like elements have been observed in adenovirions after freeze-fracturing of purified, semi-purified and intra-cellular adenovirus type 5. Their rod-like shape was clearly demonstrated by means of stereomicrographs. Ultrathin sections prepared in parallel with the freeze-fracture replicas revealed linear structures such as ribbons, rings or rods in up to 30 per cent of the semi-purified or intracellular virus particles. These observations indicate that the main 'structural element' in the adenovirus interio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1979
1979
1995
1995

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Thus they confirmed the previous reports by MalZEL et al (41) and HomvlTZ et al (84) to mention just a few of the papers. Our experience with averged right-handed GONs (45) has been that the peripheral hexons often deviate a little from the azimuth of the central ones. Similar ideas were expressed by RUSSELL et al (66), whereas PER~II~ and WI~mL~:~ ~ (55) indicated that "hexons within a nonamer are not arranged on a true p3 net" as proposed by CI~OWTI~EI~ and FRANKLIN (t5).…”
Section: The Hexonmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus they confirmed the previous reports by MalZEL et al (41) and HomvlTZ et al (84) to mention just a few of the papers. Our experience with averged right-handed GONs (45) has been that the peripheral hexons often deviate a little from the azimuth of the central ones. Similar ideas were expressed by RUSSELL et al (66), whereas PER~II~ and WI~mL~:~ ~ (55) indicated that "hexons within a nonamer are not arranged on a true p3 net" as proposed by CI~OWTI~EI~ and FRANKLIN (t5).…”
Section: The Hexonmentioning
confidence: 99%
“…High resolution electron microscopy in con-junction with new preparation techniques produced a more detailed 3D-model of the hexon, now described as a 'hollow triangular prism' (45). High resolution electron microscopy in con-junction with new preparation techniques produced a more detailed 3D-model of the hexon, now described as a 'hollow triangular prism' (45).…”
Section: The Hexonmentioning
confidence: 99%
See 2 more Smart Citations